Prevalence of overweight, obesity, and abdominal obesity in a representative sample of Portuguese adults - Sardinha, Luís B (2017)
This study determined the prevalence of overweight, obesity, and abdominal obesity in the Portuguese adults and examined the relationship between above mentioned prevalences and educational level. Body mass, stature, and waist circumference were measured in a representative sample of the Portuguese population aged 18-103 years (n = 9,447; 18-64 years: n = 6,908; ≥ 65 years: n = 2,539). Overweight and obesity corresponded to a body mass index ranging between 25-29.9 kg/m(2) and ≥ 30 kg/m(2), respectively. Abdominal obesity was assessed as >102 cm for males and >88 cm for females. After adjusting for educational level, the combined prevalences of overweight and obesity were 66.6% in males and 57.9% in females (18-64 years). Respective values in older adults (≥ 65 years) were 70.4% for males and 74.7% for females. About 19.3% of adult males and 37.9% of adult females presented abdominal obesity. Correspondent values in older adults were 32.1%, for males, and 69.7%, for females. In adults, low educational level was related to an increased risk for overweight (OR = 2.54; 95% CI: 2.08-3.09), obesity (OR = 2.76; 95% CI: 2.20-3.45), and abdominal obesity (OR = 5.48; 95% CI: 4.60-6.52). This reinforces the importance of adjusting public health strategies for educational level.